(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Black cumin is one of the most important seed spice belongs to Ranunculaceae family, used in several cooked and processed products in India due to its antimicrobial and antioxidant properties. It is commonly used as a form of traditional medicine in Middle-Eastern countries due to having high antioxidant potential and immunity boosting properties. So, this study was planned to prepare the seed extracts by using different solvents and evaluating their antioxidant activity along with the determination of total flavonoids and phenolic compounds. The analysis revealed that the highest antioxidant activity (58.08%) of methanol seed extract was obtained and the highest level of total phenolic compounds was found in ethyl acetate extract as (148.59 mg/GAE/g). Moreover, the ethyl acetate extract showed the highest flavonoids content (870.0 mg/g QE) respectively. Thus, the findings showed that a high level of natural antioxidants can be derived from Nigella sativa seed extracts by methanol solvent.